Faktor – Faktor Yang Mempengaruhi Pemilihan KB IUD Pasca Plasenta Di RSU Muslimat Ponorogo - Naning Fitriana; Tut Rayani Aksohini Wijayanti (Journal of Innovative and Creativity, 2025)
Postpartum contraception is essential because fertility can return unpredictably soon after childbirth, even before the resumption of menstruation. This study aimed to examine the factors associated with mothers’ decisions to use an intrauterine device (IUD) as a postpartum contraceptive method. A cross-sectional quantitative design was applied, involving 100 postpartum mothers recruited through purposive sampling based on established inclusion criteria. Data collection was conducted using a validated questionnaire, and data analysis employed the Chi-Square test to identify associations between variables. The findings revealed that maternal age (p < 0.05) and education level (p < 0.05) were significantly associated with the selection of postpartum IUD. In contrast, occupation (OR = 0.399), parity (OR = 0.838), type of delivery (OR = 1.528), and husband’s support (OR = 0.678) did not demonstrate significant relationships (p > 0.05). These results indicate that age and education are key determinants influencing postpartum IUD uptake, while other demographic and obstetric factors have little impact. Strengthening counseling on Long-Acting Contraceptive Methods (LACM), particularly for younger mothers and those with lower education levels, is therefore necessary to improve IUD utilization in healthcare facilities. Enhancing provider communication and ensuring that postpartum counseling is consistently integrated into maternal health services may further support informed contraceptive decision-making.